2021
DOI: 10.1186/s13048-020-00752-2
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibited metastasis through miR-145/MMP16 axis in vitro

Abstract: Ovarian cancer is the first leading cause of death in gynecological cancers. The continuous survival and metastasis of cancer cells are the main causes of death and poor prognosis in patients with ovarian cancer. Berberine is an effective component extracted from the rhizomes of coptis chinensis and phellodendron chinensis. In our study, we aim to explore the molecular mechanism underlying the regulation of proliferation, migration and invasion by berberine in ovarian cancer cells. CCK8 assay was used for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Berberine enhances the expected maximum antitumor activity of 17-AAG (the Hsp90 inhibitor) and SAHA (the HDAC inhibitor) alone in CRC (SW480) cells. The combination of the three appear the most effect ( Li J. et al, 2021 ). Magnoflorine improves the cell sensitivity to doxorubicin through inducing autophagy and apoptosis by elevating LC3-II and activating Caspase-3 via MAPK pathway in breast cancer.…”
Section: Combination Therapymentioning
confidence: 99%
“…Berberine enhances the expected maximum antitumor activity of 17-AAG (the Hsp90 inhibitor) and SAHA (the HDAC inhibitor) alone in CRC (SW480) cells. The combination of the three appear the most effect ( Li J. et al, 2021 ). Magnoflorine improves the cell sensitivity to doxorubicin through inducing autophagy and apoptosis by elevating LC3-II and activating Caspase-3 via MAPK pathway in breast cancer.…”
Section: Combination Therapymentioning
confidence: 99%
“…MiR-335 and -145 expression differs in benign and malignant tumors in women 44 , 45 . Furthermore, miR-335 and -145 were found to suppress the oncoproteins PD-L1, inhibiting the growth of breast cancer cells 46 , 47 . In the present study, using bioinformatics analysis, we identified the 3′‐UTR PD‐L1 region as a potential target for miR‐335 and -145 targeting, suggesting its possible role in the escape of immune tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the targets of BBR in cancer therapy is miRNAs. Overall, the expression level of tumor-promoting miRNAs undergoes down-regulation by BBR, while an increase occurs in expression profile of tumor-suppressor miRNAs [ 390 , 391 , 392 ]. The oral CSCs have self-renewal capacity and demonstrate high colony formation and migration abilities that are in favor of triggering drug resistance.…”
Section: Dietary Agents and Cancer Stem Cellsmentioning
confidence: 99%